Soil and root microbiome analysis and isolation of plant growth-promoting bacteria from hybrid buffaloberry (Shepherdia utahensis ‘Torrey’) across three locations - Devkota, Ananta Raj; Wilson, Ty; Kaundal, Amita (Frontiers in Microbiology, 2024)
The effects of climate change are becoming increasingly hazardous for our ecosystem. Climate resilient landscaping, which promotes the use of native plants, has the potential to simultaneously decrease the rate of climate change, enhance climate resilience, and combat biodiversity losses. Native plants and their associated microbiome form a holo-organism; interaction between plants and microbes is responsible for plants' growth and proper functioning. In this study, we were interested in exploring the soil and root microbiome composition associated with Shepherdia utahensis, a drought hardy plant proposed for low water use landscaping, which is the hybrid between two native hardy shrubs of Utah, S. rotudifolia and S. argentea. The bulk soil, rhizosphere, root, and nodule samples of the hybrid Shepherdia plants were collected from three locations in Utah: the Logan Campus, the Greenville farm, and the Kaysville farm. The microbial diversity analysis was conducted, and plant growth-promoting bacteria were isolated and characterized from the rhizosphere. The results suggest that there is no difference in alpha diversity between the locations; however, the beta diversity analysis suggests the bacterial community composition of bulk soil and nodule samples are different between the locations. The taxonomic classification suggests Proteobacteria and Actinobacteriota are the dominant species in bulk soil and rhizosphere, and Actinobacteriota is solely found in root and nodule samples. However, the composition of the bacterial community was different among the locations. There was a great diversity in the genus composition in bulk soil and rhizosphere samples among the locations; however, Frankia was the dominant genus in root and nodule samples. Fifty-nine different bacteria were isolated from the rhizosphere and tested for seven plant growth-promoting (PGP) traits, such as the ability to fix nitrogen, phosphates solubilization, protease activity, siderophore, Indole Acetic Acid (IAA) and catalase production, and ability to use ACC as nitrogen source. All the isolates produced some amount of IAA. Thirty-one showed at least four PGP traits and belonged to Stenotrophomonas, Chryseobacterium, Massilia, Variovorax, and Pseudomonas. We shortlisted 10 isolates that showed all seven PGP traits and will be tested for growth promotion.